Assessment of Variations in Round Green Tea Volatile Metabolites During Manufacturing and Effect of Second-Drying Temperature via Nontargeted Metabolomic Analysis - Wang, Huajie; Yu, Yaya; Ouyang, Wen; Jiang, Yongwen; Wang, Jinjin; Hua, Jinjie; Yuan, Haibo (Frontiers in Nutrition, 2022)
Round green tea (RGT) is widely distributed and presents a high yield in China. The quality of RGT can be determined by its aroma; however, the transformation and formation of volatile metabolites during RGT processing remain unclear. In this study, 173 volatile compounds (nine categories) were identified totally from RGT via gas chromatography-mass spectrometry with infrared-assisted headspace-solid phase microextraction. These substances exhibited different changing trends during various procedures, with the most intense transformation occurring during fixation, followed by pan-frying and second drying; moreover, 51 substances were screened, mainly containing fatty acid-derived volatiles and glycoside-derived volatiles, and their evolution during processing was clarified. Furthermore, the effect of the second-drying temperature on volatile compound metabolism was clarified, and 90 °C was the best temperature for RGT aroma. This research lays a foundation for in-depth quality control and the aroma formation mechanism of RGT.